Ecoepidemiology of paracoccidioidomycosis: A narrative review of the literature (Research, Society and Development, 2021)
Paracoccidioidomycosis is a systemic mycosis prevalent in Latin America, it is caused by Paracoccidioides brasiliensis and Paracoccidioides lutzii, which are thermodimorphic fungi, the filamentous phase is present in the soil in a saprophytic form. The objective of this work is to search presents ecoepidemiological data associating ecological and socio-environmental factors with the disease. The narrative review was carried out using the PubMed, Scielo, LILACS, MEDLINE and Google Scholar databases, where articles, theses and dissertations that addressed the topic between 2000 and 2021 were selected. A total of 35 articles, 2 dissertations, 2 theses and 1 monograph were found with a research focus on the topic of interest. The existence of other hosts, besides man, was described, mainly armadillos of the species Dazypus novemcinctus, helping to analyze the situation of territoriality, and to delimit the characteristics of the fungus ecosystem. Social and environmental changes also influence the incidence of the disease. There is a strong association in the epidemiological pattern and ecosystem of Paracoccidioides, through this analysis it is possible to predict possible outbreaks and control the disease.